PERAN JAKSA DALAM PENANGANAN PELAKU TINDAK PIDANA NARKOTIKA (Studi Kasus Penyalahgunaan Narkotika Golongan I Yang Ditangani Oleh Kejaksaan Negeri Kota Semarang) - Andita Rizkianto; Gunarto Gunarto (Jurnal Hukum Khaira Ummah, 2017)
Abuse of narcotics and drugs (drugs), especially narcotics in the city of Semarang, from year to year the number is increasing. No exception narcotics abuse, especially narcotics included in Group I with the criminal element that is handled by the Semarang City district attorney. The problems raised in this research are (1) How is the role of prosecutor in applying the element of criminal acts of narcotic abuse class I decision No. 774 / Pid.Sus / 2016 / PN Smg (2) What are the constraints and solutions related to the role of prosecutor in prosecution The handling of the perpetrators of the criminal acts of Narcotics Abuse I in Semarang City Public Prosecutor Office. The method used in this research is sociological jurisdiction, sociological juridical method is an approach that aims to describe a reality that exist in the field based on the principles of law and the legislation. The findings of this study indicate that, (1) Whereas the defendant has fulfilled the elements of the crime of article 127 paragraph (1) sub paragraph a of Law no. 35 on 2009 Narcotics proven against the law of using shabu (2) Witnesses who are mostly members of the police force, when called to witness in court are often not present in the court because of the busyness of their superiors. Solution: Prosecutors hold knowledge sharing meetings between law enforcers and improvement of management. Keywords: Role of Attorney, Narcotics Crime